SrpsEFIKASNOST HPV VAKCINE U PREVENCIJI RAKA GRLIĆA MATERICE I DRUGIH MALIGNOMAki - Simanić, Sara; Grujičić, Sandra (HEALTH CARE, 2025)
Human papillomavirus (HPV) infection is one of the most widespread sexually transmitted infections globally, responsible for a significant number of cases and deaths annually. It is one of the risk factors for cervical cancer, oral and pharyngeal cancer, vaginal cancer, vulvar cancer, penile cancer, and anal cancer, and it also causes genital warts. The introduction of licensed, globally recognized prophylactic HPV vaccines (e.g., Cervarix, Gardasil, Gardasil 9, Cecolin, Walrinvax, and Cervavac), based on virus-like particles (VLPs) made from viral protein components but without the virus's genetic material, has significantly contributed to reducing the number of cervical cancer cases, especially in highly developed countries where screening tests (Pap tests) are also used. Despite the introduction and implementation of these vaccines, HPV-related malignancies continue to be a global problem. The aim of this review is to analyze the effectiveness of the HPV vaccine in preventing cervical cancer and other malignant tumors.
Keywords: human papillomavirus (HPV), vaccine, incidence, cervical cancer, efficacy, vaccination coverage